Waste flame-retardant polyurethane foam/ground tire rubber/carbon nanotubes composites with hierarchical segregated structures for high efficiency electromagnetic interference shielding. (June 2023) - Zhang, Jian; Wang, Qunhao; Xue, Xiaolin; Li, Mei; Sun, Xunwen; Zhao, Jiangqi; Zhang, Wei; Lu, Canhui
Graphical abstract: Highlights: WCC is prepared to serve as a stable 3D conductive skeleton for flexible CPC. The GTR/CNT powder mixture fills the voids of WCC to form hierarchical segregated structures. The WCC/GC composite exhibits superb and stable EMI shielding performance. The WCC/GC composite is mechanically strong with high flame retardancy. The CPC has social and economic benefits as is derived from polymer wastes. Abstract: Recently, flexible conductive polymer composites (CPCs) have attracted increasing interests for their promise in electromagnetic interference (EMI) shielding. Inspired by the "steel reinforced concrete" structure, we proposed in this study a novel method to prepare a CPC with high EMI shielding performance from waste flame-retardant polyurethane foam (WFPUF) and ground tire rubber (GTR). In this CPC, WFPUF coated with carbon nanotubes (CNT) and cellulose nanofibers (CNF) served as a strong and conductive skeleton like the "steel" in "steel reinforced concrete". Meanwhile, the GTR and CNT composite with a segregated structure occupied the pore space of WFPUF/CNT/CNF (WCC) to form the WCC/GTR/CNT composite, similar to the "concrete" in "steel reinforced concrete". Owing to such a hierarchical structure, the resultant WCC/GTR/CNT demonstrated some coveted properties, including the enhanced mechanical properties, high electrical conductivity (84.0 S·m −1 ), excellent EMI shielding performance (53.8 dB), and long-term durability. Remarkably, the composite also showed great flame retardancy due to the presence of WFPUF. This work provided a promising strategy for the preparation of eco-friendly, low cost, flexible and efficient CPCs from polymer wastes, which showed high potential in EMI shielding.